2011
DOI: 10.1016/j.ijporl.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial hearing of normally hearing and cochlear implanted children

Abstract: ObjectiveSpatial hearing uses both monaural and binaural mechanisms that require sensitive hearing for normal function. Deaf children using either bilateral (BCI) or unilateral (UCI) cochlear implants would thus be expected to have poorer spatial hearing than normally hearing (NH) children. However, the relationship between spatial hearing in these various listener groups has not previously been extensively tested under ecologically valid conditions using a homogeneous group of children who are UCI users. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 45 publications
12
52
1
Order By: Relevance
“…Compared to the present data, mean absolute errors of localization were somewhat smaller (from 5° for 4-year-olds to 1° for 6-year-olds), but in this study the speakers were visible and positive feedback was provided for correct answers, which might have made the task easier as learning effects cannot be excluded. We can, therefore, reasonably assume that from 6 years onwards, no further improvement of localization accuracy occurs, as also shown by Murphy et al [2011].…”
Section: Auditory Localization Accuracy Matures Earlier Than Spatial supporting
confidence: 57%
“…Compared to the present data, mean absolute errors of localization were somewhat smaller (from 5° for 4-year-olds to 1° for 6-year-olds), but in this study the speakers were visible and positive feedback was provided for correct answers, which might have made the task easier as learning effects cannot be excluded. We can, therefore, reasonably assume that from 6 years onwards, no further improvement of localization accuracy occurs, as also shown by Murphy et al [2011].…”
Section: Auditory Localization Accuracy Matures Earlier Than Spatial supporting
confidence: 57%
“…The spatial hearing advantage in BiCI users is also reflected in the results from self-assessment questionnaires for both adults and children, although in the latter case the data are considerably noisier. The advantage appears not to be due to greater familiarity with the bilateral condition compared to the monaural condition when testing BiCI users because comparable improvements are seen relative to actual unilateral CI users (Dunn et al, 2010b;Murphy et al, 2011). The benefits available from a contralateral hearing aid in bimodal listeners are in contrast not strongly related to spatial hearing, and instead derive more from the provision of information that is unavailable through the cochlear implant.…”
Section: Discussionmentioning
confidence: 95%
“…However, these children have the benefit of developing bilateral auditory pathways in tandem (30,38Y40) without the risk that one side is strengthened at the expense of the other as exists when stimulation is provided unilaterally for extended periods. Early data suggest that these children show more normal bilateral listening abilities than their peers receiving bilateral implants sequentially (27,39) and that, when bilateral implants are provided early and simultaneously, speech and language skills develop rapidly (12). A study comparing 25 unilateral implanted children with 25 bilaterally implanted children (all implanted before 2.06 years of age and carefully matched) found that bilateral implants are associated with better spoken language learning and that a longer interval between implants adversely affected the scores (41).…”
Section: Reported Outcomes Of Simultaneous Bilateral Implantationmentioning
confidence: 99%